Teachers’ Beliefs of Using Multimodal Resources in Teaching English Skills - Jenni Ferstephanie; Theodesia Lady Pratiwi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
It is undeniable that language learning can be communicated through various modes. The innovation of technology has changed the way people read, write, and thought. Multimodal resources are defined as a medium communication that played important role in conveying the message that contained meaning. The research objective was to identify types of multimodal resources that teachers used in teaching English skills. Furthermore, this study aimed to define the teachers' perceived and reflected on using multimodal resources in teaching English skills. The research was conducted using a mixed-method design with an explanatory sequential design. The researcher utilized questionnaires, classroom observation, and in-depth interviews as the research instruments. The participants in the research were UIB English teachers with a total of 10 English teachers. The result of the study showed that the highest percentage of multimodal resources were speech (94%), facial expressions (92%), graphics (90%), and pictures (90%), and the lowest percentage of multimodal resources were physical movement (80%), music (80%), and writing (82%). In addition, this study also found out that teachers showed positive attitudes to the use of multimodal resources in teaching English skills. Teachers believed that multimodal resources were a communication bridge between the teachers and students in the class. The use of multimodal resources in English learning facilitated teachers to deliver the lesson materials easily. Therefore, the utilization of multimodal resources was significantly important in teaching English skills. It was found that the use of multimodal resources engaged the teachers and students to achieve meaningful language learning.